KAJIAN PELAYANAN ANTENATAL K4 DAN PERTOLONGAN PERSALINAN DI PUSKESMAS KABUPATEN PATI - Nafiah, Ulin; Setiawati, Indayana (Jurnal Litbang: Media Informasi Penelitian, Pengembangan dan IPTEK, 2019)
ENGLISHThe services of K4 pregnant women are a complete range of antenatal services that meet minimum service standards. This study aim was to analyze the implementation of antenatal K4 in the Community Health Center of Pati District. This research used a qualitative approach with phenomenological evidents, to provide an overview of the experiences of midwives in antenatal K4 and delivery assistance in community health centers in order to reduce MMR. The main informants were 5 midwives and triangulation including 2 head of the community health center, 2 doctors at the community health center, and 1 head of the family health section. The research used purposive sampling. The results showed that the K4 service at the community health center was carried out by midwives and doctors, with its operational application known as a minimum service standard (10T). Most childbirth assistance has been conducted at the community health center by midwives and doctors (on call). If complications are found in childbirth, the midwife will coordinate with the clinic doctor to make a referral letter. K4 coverage has not been fulfilled so it is necessary to promote K4 antenatal services to the community. INDONESIAPelayanan ibu hamil K4 merupakan  cakupan pelayanan antenatal secara lengkap yang memenuhi standar pelayanan minimal. Penelitian ini bertujuan untuk menganalisis pelaksanaan pelayanan antenatal K4 di Puskesmas Kabupaten Pati. Penelitian menggunakan pendekatan kualitatif dengan pendekatan fenomenologis, untuk memberikan gambaran tentang pengalaman bidan dalam program K4 dan pertolongan persalinan di Puskesmas dalam rangka menurunkan Angka Kematian Ibu (AKI). Informan utama 5 bidan dan triangulasi pada 2 Kepala Puskesmas, 2 dokter Puskesmas, dan 1 Kepala Seksi Kesehatan Keluarga. Teknik sampling menggunakan teknik purposive sample. Hasil penelitian menunjukkan bahwa pelayanan K4 di Puskesmas dilaksanakan oleh bidan dan dokter dengan penerapan operasionalnya dikenal standar pelayanan minimal (10T). Pertolongan persalinan sebagian besar sudah di Puskesmas oleh bidan dan dokter (on call). Jika ditemukan penyulit dalam persalinan, bidan akan berkoordinasi  dengan dokter puskesmas untuk membuat surat rujukan. Cakupan K4 belum terpenuhi sehinggga perlu promosi pelayanan antenatal K4 kepada masyarakat.